A CO2-responsive smart fluid based on supramolecular assembly structures varying reversibly from vesicles to wormlike micelles. Issue 42 (3rd July 2020) - Xiong, Chunming; Wei, Falin; Zhou, Qiang; Peng, Kang; Ye, Zhengrong; Yang, Haiyang
Abstract : CO2 -responsive smart fluids have been widely investigated in the past decade. In this article, we reported a CO2 -responsive smart fluid based on supramolecular assembly structures varying from vesicles to wormlike micelles. Abstract : CO2 -responsive smart fluids have been widely investigated in the past decade. In this article, we reported a CO2 -responsive smart fluid based on supramolecular assembly structures varying from vesicles to wormlike micelles. Firstly, oleic acid and 3-dimethylaminopropylamine reacted to form a single-chain weak cationic surfactant with a tertiary amine head group, N -[3-(dimethylamino)propyl]oleamide (NDPO). Then, 1, 3-dibromopropane was used as the spacer to react with NDPO to form a gemini cationic surfactant, trimethylene α, ω-bis(oleate amide propyl dimethyl ammonium bromide) (GCS). By controlling the feed ratio of 1, 3-dibromopropane and NDPO, we found that the mixtures of GCS and NDPO with the molar ratio of 7 : 3 approximately could form vesicles in aqueous solution by supramolecular self-assembly. After bubbling CO2, the tertiary amine of NDPO was protonated. The packing parameter of the mixed surfactants reduced accordingly, accompanied by the transition of aggregates from vesicles to wormlike micelles. As a result, the zero-shear viscosity of the solution increased by more than four orders in magnitude. When the solid content of GCS/NPDO mixtures was higher than 5 wt% in solution, the sample treated by CO2 behaved as a gel over a wide frequency range with shear-thinning and self-healing properties. In addition, the sol–gel transition could be repeatedly and reversibly switched by cyclically bubbling CO2 and N2 . Our effort may provide a new strategy for the design of CO2 -responsive smart fluids, fostering their use in a range of applications such as in enhanced oil recovery.